The impact of 9-azaglycophymine and phenylguanidine derivatives on the proliferation of various breast cancer cell lines in vitro and in vivo - Ibrahim Morgan; Robert Rennert; Robert Berger; Sanja Jelača; Danijela Maksimović-Ivanić; Duško Dunđerović; Sanja Mijatović; Goran N. Kaluđerović; Ludger A. Wessjohann (Scientific Reports)
Abstract Quinazolinones, particularly 9-azaglycophymines, and closely related derivatives and precursors were tested in vitro against various breast cancer cell lines representing the major types of breast tumors. Among the 49 compounds tested, azaglycophymine derivative 19 with an electron-withdrawing substituent demonstrated the most significant anti-proliferative effects, with IC50 values of around 4 µM. Extensive cell-based investigations revealed that compound 19 induced caspase-dependent apoptosis in HCC1937 (human TNBC), BT-474 (human HER2+/HR+), and 4T1 (mouse TNBC) cells. In contrast, in MDA-MB-468 (human TNBC) and MCF-7 (human HR+) cells, the cell death was induced via a non-apoptotic pathway. The in vivo efficacy of compound 19 was validated using a syngeneic orthotopic 4T1 model in BALB/c mice, resulting in significant reduction of 4T1 breast tumor growth upon intraperitoneal (i.p.) application of doses of 5 or 20 mg/kg. These findings highlight the potential of compound 19 as a promising scaffold for the development of new therapeutic agents for various types of breast cancer and a first structure-activity insight.